Various types of isopolymolybdate-based metal–organic complexes formed in different conditions: synthesis, structures, luminescence, electrochemical, and photocatalytic performances. Issue 42 (10th October 2019) - Pan, Xiang; Wang, Xiuli; Wang, Xiang; Li, Yan; Liu, Guocheng; Lin, Hongyan
Abstract : A series of isopolymolybdate-based complexes of different metals and ligands were prepared, which exhibited different luminescence behaviors, current sensing activities, and photocatalytic MB performances. Abstract : Under the regulation of different metal ions and organic ligands, five isopolymolybdate-based complexes, namely, [CoL 1 0.5 (Mo3 O10 )(H2 O)2 ]·2H2 O (1 ), [NiL 1 0.5 (Mo3 O10 )(H2 O)2 ]·2H2 O (2 ), [ZnL 1 (H2 O)3 ][γ-Mo8 O26 ]0.5 (3 ), [CdL 1 1.5 (θ-Mo8 O26 )0.5 ]·2H2 O (4 ), and [ZnL 2 (Mo3 O10 )]·H2 O (5 ) (L 1 = 1, 4-bis(1 H -pyrazole-4-carboxamide) p -phenylene, L 2 = 1, 2-bis(1 H -imidazole-4-carboxamido)ethyl) were prepared under hydrothermal/solvothermal conditions. Complexes 1, 2, and 4 were obtained under solvothermal conditions. 1 and 2 were isostructural, composed of [M2 L 1 (H2 O)4 ] 4+ (M = Co II /Ni II ) cationic units and [Mo3 O10 ] n 2 n − polymolybdate chains. In the presence of Cd ions, the 2D network structure of 4 was constructed from the [θ-Mo8 O26 ] 4− anions bridged by metal–organic belts. Both 3 and 5 were isopolymolybdate-based Zn II -complexes synthesized under hydrothermal conditions except for the difference of organic ligands and pH, namely, L 1 acted as the ligand and the pH was 3.5 for 3, but they were L 2 and 3.4 for 5, respectively. Complex 3 had a 2D supramolecular structure containing cationic units ZnL 1 (H2 O)3 2+ and 1D infinite inorganic chains [γ-Mo8 O28 ] n . In 5, the 1D convergent chains [Mo3 O10 ] n were connected by binuclear metal–organic cationic rings [Zn2 L 2 2 ] 4+ to form a 2D structure. The solvent ratio and reaction pH had a great influence on the synthesis of the title complexes, and metal ions and ligands played important roles in regulating the diversity of the polymolybdates and the structures of the complexes. The electrochemical, luminescence, and photocatalytic degradation properties for MB of the title complexes were investigated.